Analisis Environmental-DNA (E-DNA) Untuk Estimasi Jumlah Total Bakteri Pada Air Kolam dengan Sistem Recirculation Aquaculture System (RAS - Kurniawan, Andi; Amin, Abd. Aziz; Guntur, Guntur; Susanti, Yogita Ayu Dwi; Wiryawan, Adam; Pramudia, Zulkisam; Okuda, Hideki; Yanuar, Adi Tiya (Universitas Trunojoyo Madura, 2022)
Catfish is an aquaculture commodity that has great potential to be developed in various regions in Indonesia. The success of catfish cultivation is primarily determined by creating a suitable environment for catfish. One way to create a suitable environment for catfish cultivation is the Recirculation Aquaculture System (RAS). In applying RAS, the presence of organic matter in the pond is controlled so the pond water can be reused. The presence of organic matter in pond water is determined mainly by the activity of bacteria in the water. These bacteria are actively involved in the pond's residual organic matter degradation process. Therefore, the total number of bacteria in the water can be one of the essential parameters in the RAS. The method widely used to calculate the abundance of bacteria is counting the number of bacteria based on bacterial culture method. However, the bacteria that can be cultured are only a small part of the bacteria in the water, so the abundance value obtained does not reflect the actual bacterial population. Therefore, it is necessary to analyze the abundance of bacteria using a method closer to the actual abundance value, such as the environmental DNA (eDNA) analysis. This study aims to analyze the abundance of bacteria in water in catfish aquaculture with RAS using the eDNA method. In addition, this study also analyzes water quality data (temperature, pH, Dissolved Oxygen). This study's results indicate that the water temperature value in catfish ponds ranges from 28.0 to 29.0 °C, the average pH value is 7.7, and the dissolved oxygen is between 5.7 - 6.2 mg/L. The water quality analysis results indicate that RAS can maintain optimum conditions in the catfish cultivation process. This study also showed that the total microbial abundance value at the beginning of cultivation was 1.68 × 107 cells/ml, and on day 30, it was 3.6 × 106 cells/ml. The dynamic of bacterial densities in this study may indicate that this system can maintain the stability of the microbial community.